A Listeria ivanovii balanced‐lethal system may be a promising antigen carrier for vaccine construction. Issue 11 (7th September 2022) - Lei, Yao; Zhou, Yuzhen; Zhang, Yunwen; Liu, Sijing; Tian, Sicheng; Ou, Qian; Liu, Ting; Huang, Huan; Tang, Tian; Wang, Chuan
Abstract: Expressing heterologous antigens by plasmids may cause antibiotic resistance. Additionally, antigen expression via plasmids is unstable due to the loss of the plasmid. Here, we developed a balanced‐lethal system. The Listeria monocytogenes (LM) balanced‐lethal system has been previously used as an antigen carrier to induce cellular immune response. However, thus far, there has been no reports on Listeria ivanovii (LI) balanced‐lethal systems. The dal and dat genes from the LI‐attenuated LIΔ atcAplcB (LIΔ) were deleted consecutively, resulting in a nutrient‐deficient LIΔdd strain. Subsequently, an antibiotic resistance‐free plasmid carrying the LM dal gene was transformed into the nutrient‐deficient strain to generate the LI balanced‐lethal system LIΔdd: dal . The resultant bacterial strain retains the ability to proliferate in phagocytic cells, as well as the ability to adhere and invade hepatocytes. Its genetic composition was stable, and compared to the parent strain, the balanced‐lethal system was substantially attenuated. In addition, LIΔdd: dal induced specific CD4 + /CD8 + T‐cell responses and protected mice against LIΔ challenge. Similarly, we constructed an LM balanced‐lethal system LMΔdd: dal . Sequential immunization with different recombinant Listeria strains will significantly enhance the immunotherapeutic effect. Thus, LIΔdd: dal combined with LMΔdd: dal, or with other balanced‐lethal systems will be more promising alternative for vaccine development. Abstract : The attenuated LI and LM balanced‐lethal stable systems were successfully constructed. LIΔdd: dal can proliferate in phagocytic cells and invade non‐phagocytic cells. LIΔdd: dal can induce cellular immune responses and enhance the protection against LIΔ.